Tinjauan Yuridis Proses Alih Status Pegawai Komisi Pemberantasan Korupsi - Aryananta, Mega Pamungkas; Cahyo Nugroho, Widhi (Journal Evidence Of Law, 2023)
Human rights and democracy are concepts of communion and social relations that were born from the history of human culture. Therefore, the notion of Indonesia being a rule of law is related to the concepts of human rights and democracy, and in fact what governs is the law, not the people. The MPR also established a legal umbrella for human rights with number XVII/MPR/1998. Based on this, a legal regulation was issued, namely Law Number 39 of 1999 concerning Human Rights (UU HAM), which has a vital capacity related to the most common ways of human rights in Indonesia. Recently, there was a case where there was an alleged act that was contrary to human rights, this involved KPK employees carrying out the National Insights Test (TWK) with the aim of changing the status of the previous status only as KPK but had to be transferred as a State Civil Apparatus. (ASN). The transfer of status of KPK Employees to ASN Employees with the TWK method as mandated by Perkom KPK Number 1 of 2021 is not fundamental to the regulations above, namely PP Number 41 of 2020 because the PP does not imply the existence of TWK implementation, and relates to the questions given during the TWK assessment with the interview method indicates human rights violations as regards the rights that have been violated that have been guaranteed by the 1945 Constitution and the Human Rights Law. With regard to Komnas HAM's authority to carry out investigations, it can only be carried out in cases of Serious Human Rights Violations (Crime of Genocide and Crimes against Humanity) while in cases of transferring the status of KPK employees it does not include Serious Human Rights Violations, as well as regarding the strength of recommendations that are non-binding and do not have sanctions in them, so that Komnas HAM's recommendations are relatively weak.